Processing math: 12%
 
+0  
 
0
465
3
avatar+43 

5-2(4a+1)+3a=13

 May 14, 2021
 #1
avatar+876 
0

$5-2(4a+1)+3a=13$

$5-(8a+2)+3a=13$

$(-8a+3a)+(5-2)=13$

$(-8+3)a+3=13$

$-5a=10$

$a=\frac{10}{-5}=-\frac{10}{5}=\boxed{-2}$

 May 14, 2021
 #2
avatar
0

your anwer is.........

𝑎=−2     

 May 14, 2021
 #3
avatar+373 
+2

Hey there, Caydog!

 

So let's solve this.

 

Step 1: Simplify both sides of the equation.

52(4a+1)+3a=13

 (Distribute)

 (Combine Like Terms)

 

Step 2: Subtract 3 from both sides.

 

Step 3: Divide both sides by -5.

 

Therefore a=-2.

 

Hope this helped! :)

( ゚д゚)つ Bye

 May 14, 2021

2 Online Users

avatar
avatar